Development of Polymer E-Modules in Solution, Solids, and Amorphous Based on Problem-Based Learning - Rani Safitri; Sanjaya; Eka Ad’hiya; Andi Suharman; M. Hadeli (Chemistry Education Department of Education and Teaching Faculty, 2024)
This research was conducted with the aim to produce E-Modules of polymers in solution, solids, and amorphous based on problem-based learning that are valid, practical and effective. This research used the 4S-TMD (Four Steps Teaching Material Development) research model which consists of four stages, namely selection, structuring, characterization, and didactic reduction. After the material validity test was conducted by two expert lecturers. The material validation score was 0.96; pedagogical validation 1; and design validation 1. The practicality of this E-Module is proven by getting an average score of 95.7%, which is classified as very practical. In addition, the effectiveness test using the N-Gain value reached 0.91 (high category).. Based on this value, it shows that the E- Module of polymers in solutions, solids, and amorphous based on problem-based learning has achieved valid practical and effective criteria.